Generating and monitoring mild hyperthermia using a ring array ultrasound transducer - David Bustamante; Yan Yan; Trevor Mitcham; Rehman Ali; Brian Marples; Kimberly R. Gergelis; Peter Littrup; Nebojsa Duric; Mohammad Mehrmohammadi (International Journal of Hyperthermia)
Objective To demonstrate the feasibility of using a ring array ultrasound (US) transducer, guided by ultrasound tomography (UST), for generating and monitoring mild hyperthermia (MHTh).Methods In silico and in vitro experiments were designed to evaluate the efficacy of a ring array US transducer for generating MHTh and monitoring changes in temperature. In a series of in silico studies, we compared the acoustic focal profiles produced by a ring array US transducer transmitting at different frequencies and further investigated the effectiveness of UST-guidance in implementing aberration correction to enhance the focal profile. In vitro experiments evaluated the capability of using a ring array US transducer to generate and maintain MHTh and the accuracy of using UST to monitor temperature changes.Results The simulations demonstrated that a ring array US transducer achieves symmetrical and localized acoustic focusing. In a heterogenous tissue model, a ring array US transducer achieved a superior acoustic focus by implementing aberration correction with guidance from UST. In vitro experiments demonstrated the capability of a ring array US transducer to generate MHTh in a tissue-mimicking phantom in an average of 117 ± 18 s and subsequently maintain MHTh. Lastly, a ring array US transducer utilized UST to track temperature changes in a preheated water-filled inclusion while it passively cooled from 45 °C to 25 °C, with a maximum error of 0.58 °C.Conclusion A ring array US transducer can noninvasively generate and monitor MHTh, overcoming many limitations of current clinical systems. The closed geometry of the transducer is optimal for acoustic focusing and UST-guidance allows for improved aberration correction in a heterogenous medium. Utilizing UST thermometry with the same ring array US transducer will allow for implementing an image-guided, temperature-controlled, all-acoustic MHTh system.